2012
DOI: 10.5586/aa.2012.021
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of flowering and pollen release of selected herbaceous plants in Szczecin and Gudowo (Western Pomerania) and the risk of pollen allergy

Abstract: A b s t r a c tThis paper presents the course of the pollen season of selected allergenic taxa (Secale spp., Rumex spp., Plantago spp., Urtica spp., Artemisia spp., Chenopodiaceae and Poaceae) in Szczecin (2009) and Gudowo (Western Pomerania, Poland) (2009)(2010), and also the flowering pattern of Chenopodium album, Artemisia vulgaris and Secale spp. Pollen deposition was studied by the gravimetric method using a Durham sampler. In 2010 the flowering period of the studied taxa was shorter than in 2009 and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…Spearman correlation coefficients indicated that higher temperatures, radiation and sunshine duration were connected with a higher pollen grain count, while higher relative humidity coincides with lower concentrations. In contrast to M a l k i e w i e c z et al [43] and K r u c z e k and P u c [30], we did not find a correlation for wind speed. Additionally, M a l k i e w i c z et al [43] also noted that higher correlation coefficients were obtained for weather parameters over periods from several days to a month, rather than for weather parameters on a given day.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Spearman correlation coefficients indicated that higher temperatures, radiation and sunshine duration were connected with a higher pollen grain count, while higher relative humidity coincides with lower concentrations. In contrast to M a l k i e w i e c z et al [43] and K r u c z e k and P u c [30], we did not find a correlation for wind speed. Additionally, M a l k i e w i c z et al [43] also noted that higher correlation coefficients were obtained for weather parameters over periods from several days to a month, rather than for weather parameters on a given day.…”
Section: Discussioncontrasting
confidence: 55%
“…Peak concentrations occur earlier in natural habitats, and in suburban areas rather than in cities, and the peaks in the latter are usually lower. Preliminary studies conducted in SE and NW Poland seem to confirm this thesis [19,30].…”
Section: Introductionsupporting
confidence: 57%
“…This fact is of concern since it implies not only an earlier peak in the pollen season but a reduction in the interval between first and full flowering suggesting a greater pollen load over a shorter time span. This is important for constructing calendars for allergy sufferers (Myszkowska et al 2011 ; Kruczek and Puc 2012 ; Ziello et al 2012 ) and supports the view that these calendars should be changed over time (Ziello et al 2012 ). A similar shortening of the flowering period was reported for native and exotic species by Bock et al ( 2014 ).…”
Section: Discussionmentioning
confidence: 67%
“… 2011 ). In Poland, winter rye is considered to be a major allergen (Myszkowska et al 2011 ; Kruczek and Puc 2012 ). Analysis of phenological data is thus also important to generate a regional pollen calendar and to predict the periods of increased pollen counts, which are important to know for the treatment of pollinosis (Kruczek and Puc 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although aeromycological research is rare, there are plenty of Polish studies that examine the relationship between flowering and the course of pollen seasons, e.g., for tree species such as Alnus glutinosa, Alnus incana (Dąbrowska & Kaszewski, 2012;Kasprzyk, 2003;Pidek, 2007;Stępalska et al, 2016), Corylus avellana (Puc & Kasprzyk, 2013;Stępalska et al, 2016), Betula pendula (Kasprzyk, 2003), Populus wilsonii, Ulmus laevis, Salix caprea, Aesculus hippocastanum and Tilia cordata (Stach, 2006). In addition, observations of the flowering of several species of herbaceous plants in relation to airborne pollen were conducted in Szczecin (Kruczek & Puc, 2012). e comparative analysis of flowering phenology and pollen seasons allows the identification of species that have the most significant impact on pollen abundance.…”
Section: Relationship Between Phenology and Bioaerosols Concentrationmentioning
confidence: 99%